Solar based wireless on road charging station for electric vehicles. (2021) - Kandasamy, V.; Keerthika, K.; Mathankumar, M.
Abstract: Electric vehicle (EV) emerging as an upcoming technology in both the sector of transportation and power. There are more benefits in terms of economic and environmental conditions. The most important factor in Electric Vehicle is charging station, which reduces a green gas effect and environment pollution. This electric charging station is also known as Electric Vehicle Supply Equipment (EVSE). It consists of both the high power and low power. The high power is terminated at a fraction of second charging that can be implement in the Electric vehicle rather than the low power so, if we construct an on-road charging with the help of solar panel it will be very useful to charge at any point of time and with the help of connected batteries we can drive in off road. Remote force move technique is fused in moving the sunlight-based force from the Photo Voltaic (PV) cell to the battery utilized in the electric vehicle. Sun oriented boards are considered to assemble an independent force station, along these lines limiting its reliance on ordinary energy assets. The sun-oriented boards create electrical energy by the utilization of the light energy produced by the sun. The energy acquired from the board is taken care of to a battery, through a sunlight-based charge regulator which augments the force yield from the PV cell. The communicating coil with the receiving coil are connected wirelessly and thus the DC current is injected to the battery. Once the battery is full it automatically turned off from solar power. Thus, it results in sustainable transportation and use of Electric batteries. The charging stations are outlined and the impact of electric vehicle are also discussed.